Shifting voices: A comparison of two novelists’ translations of a third - Davies, Eirlys E. (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThis paper compares the English and French translations of Mohamed Choukri’s autobiographical work originally written in Arabic under the title Al khubs al hafi. The translations are somewhat unusual in that both were published long before the source text became available, and in that they were done by two renowned novelists (Paul Bowles and Tahar Ben Jelloun) while Choukri himself was a completely unknown writer. The comparison reveals many contrasts. The English version favours a fragmentary, often disjointed style, with simple everyday vocabulary and frequent repetition, while the French version uses more sophisticated syntax and more specialised and varied lexis. There are also differences in content; the English version often remains more implicit than the French and yet provides more horrific details, and it frequently opts for foreignization where the French features the strategy of domestication. It is suggested that these contrasts reflect the ways in which the novelists’ own voices have influenced the way in which they express the voice of Choukri.